Rhinovirus exposure impairs immune responses to bacterial products in human alveolar macrophages. Issue 6 (1st February 2008) - Oliver, B G G; Lim, S; Wark, P; Laza-Stanca, V; King, N; Black, J L; Burgess, J K; Roth, M; Johnston, S L
Abstract : Background: Rhinovirus infection is responsible for considerable morbidity and mortality as the major cause of exacerbations of asthma, and is also known to induce exacerbations of cystic fibrosis and chronic obstructive pulmonary disease. Exacerbations of these diseases are also frequently associated with bacterial and atypical bacterial infection. Alveolar macrophages are the major immune cells in the airways and are important in defence against bacterial infections. Methods: The authors investigated whether rhinovirus modifies cytokine release, the pattern recognition receptor expression and phagocytosis by human alveolar macrophages in response to bacterial products. Results: Viable rhinovirus was detected in macrophages up to 3 days after exposure and viral RNA expression persisted for 10 days. Infectious but not UV inactivated rhinovirus increased tumour necrosis factor α (TNFα) and interleukin (IL)8 release by macrophages. In contrast, infectious rhinovirus impaired lipopolysaccharide and lipoteichoic acid induced TNFα and IL8 secretion by macrophages. Rhinovirus induced impairment of macrophage antibacterial immune responses did not involve IL10, prostaglandin E2 or downregulation of Toll-like receptor 2. Furthermore, the macrophage phagocytic response to labelled bacterial particles, but not to latex beads, was impaired. Conclusion: The authors have identified impairment of cytokine responses to bacterial lipopolysaccharide and lipoteichoic acid by alveolar macrophages in response to infectious rhinovirus. Virus induced impairment of antibacterial host defence has important implications in the pathogenesis of exacerbations of respiratory diseases.